Vocational High School 5 Telkom Banda Aceh's Occupational Safety and Health Module Design - Hasna Sari; Muhammad Rizal Fachri; Raihan Islamadina (PTE FTK UIN Ar-Raniry, 2024)
In educational institutions, occupational safety and health are significant issues. Students and institutions may suffer losses as a result of accidents and issues with occupational health. Thus, it's critical that pupils have comprehensive understanding of K3. SMK Negeri 5 Telkom Banda Aceh observations revealed a deficiency in instructional resources for K3 instruction. Therefore, the goal of the research is to use the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) in conjunction with the Research and Development (R&D) technique to design an Occupational Safety and Health Module. Student response questionnaires, validation questionnaires from media experts, and material experts were used in the data collection process. According to the research findings, 92.5% of material experts and 77.5% of media experts believe that the K3 module is adequate from a media standpoint. Student responses also attain a score of 92.4%, suggesting that the K3 module is appropriate for use in education. In summary, the K3 module has emerged as a highly successful educational tool for maximizing students' engagement with K3.